2007
DOI: 10.1089/jwh.2006.0191
|View full text |Cite
|
Sign up to set email alerts
|

Work and Marital Status in Relation to Depressive Symptoms and Social Support among Women with Coronary Artery Disease

Abstract: In women with CAD, all <65 years of age, after a cardiac event, patients working had lower levels of depressive symptoms and a better social integration than those not working, regardless of reason for being nonemployed. Daily stress behavior, depression, and social support did not differ between cohabiting and not cohabiting women. Future interventions should take into consideration that women with CAD who are unemployed may have a higher risk for depression and social isolation and, therefore, poor clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 54 publications
2
7
0
2
Order By: Relevance
“…Regarding the research hypotheses, consistent with the results of previous research (e.g., Blom et al, 2007;Carlson et al, 2006;Kulik & Liberman, 2013), a larger number of roles was significantly associated with a sense of MIL among working parents (supporting Hypothesis 1). However, occupying a large number of roles was related only to the experience of WIF conflict and not to FIW conflict (partially supporting Hypothesis 2).…”
Section: Discussionsupporting
confidence: 88%
“…Regarding the research hypotheses, consistent with the results of previous research (e.g., Blom et al, 2007;Carlson et al, 2006;Kulik & Liberman, 2013), a larger number of roles was significantly associated with a sense of MIL among working parents (supporting Hypothesis 1). However, occupying a large number of roles was related only to the experience of WIF conflict and not to FIW conflict (partially supporting Hypothesis 2).…”
Section: Discussionsupporting
confidence: 88%
“…17,19,20 The current study is the first to demonstrate the longitudinal association between divorce and AMI and extends our understanding of lifetime exposure to social stressors and cardiovascular risks. The results of this study contribute to mounting evidence that AMI risks associated with social stressors are of the relative magnitude of established risk factors such as smoking, diabetes, and hypertension.…”
Section: Discussionsupporting
confidence: 57%
“…The direction of effects of employment status on depression in women, in general, is inconsistent; some research has shown that working protects against depression [40], yet other research has found that working does not reduce and can even increase the experience of depressed mood [41]. Although controls with multiple caregiving roles were less likely to be depressed at the 12-month follow-up compared with baseline, controls, but not patients, who identified themselves as homemakers were twice as likely to report elevated depressed mood as controls who were working at least part time.…”
Section: Discussionmentioning
confidence: 99%